Curcumin and its demethoxy derivatives possess p300 HAT inhibitory activity and suppress hypertrophic responses in cardiomyocytes - Yoichi Sunagawa; Masafumi Funamoto; Shogo Sono; Kana Shimizu; Satoshi Shimizu; Mai Genpei; Yusuke Miyazaki; Yasufumi Katanasaka; Eriko Morimoto; Morio Ueno; Maki Komiyama; Hideaki Kakeya; et al. (Elsevier, 2018)
The natural compound, curcumin (CUR), possesses several pharmacological properties, including p300-specific histone acetyltransferase (HAT) inhibitory activity. In our previous study, we demonstrated that CUR could prevent the development of cardiac hypertrophy by inhibiting p300-HAT activity. Other major curcuminoids isolated from Curcuma longa including demethoxycurcumin (DMC) and bisdemethoxycurcumin (BDMC) are structural analogs of CUR. In present study, we first confirmed the effect of these three curcuminoid analogs on p300-HAT activity and cardiomyocyte hypertrophy.Our results showed that DMC and BDMC inhibited p300-HAT activity and cardiomyocyte hypertrophy to almost the same extent as CUR. As the three compounds have structural differences in methoxy groups at the 3-position of their phenol rings, our results suggest that these methoxy groups are not involved in the inhibitory effects on p300-HAT activity and cardiac hypertrophy. These findings provide useful insights into the structure-activity relationship and biological activity of curcuminoids for p300-HAT activity and cardiomyocyte hypertrophy. Keywords: Curcumin, Demethoxycurcumin, Bisdemethoxycurcumin, p300, Cardiomyocyte hypertrophy